ANALISIS TINGKAT KESIAPAN DAN KEMAMPUAN MAHASISWA PEKERJA DI MEDAN DALAM MENGHADAPI MASYARAKAT EKONOMI ASEAN (MEA) - Lusiah Lusiah (Jurnal Ilmiah Manajemen Muhammadiyah Aceh, 2015)
This study aims to determine the influence level of readiness that consists of physical readiness and mental readiness as well as the ability consisting of intellectual ability and physical ability on the competitiveness of college student workers who is working in Medan on facing the ASEAN Economic Community (AEC).The method used in this research is descriptive quantitative research methods. The analytical method used is multiple linear regression analysis and hypothesis testing which consists of partial test (t test), simultaneous test (F test) and also determination test. The population of this research is all college student workers at five private universities in Medan that is STIE-STMIK IBBI, STMIK-STIE Mikroskil, STIE-STBA-STMIK ITMI, UNPRI, STBA-PIA which amounts to 13.628 people. The sampling technique in this study using Non Probability Sampling technique namely purposive sampling, constitute the sampling technique with certain considerations, that is college students who are already working. Determination of the number of samples taken as respondents in this study using slovin method obtained by 99 people.